Gender role perception and choice of vocation - De, Ksuhal andSin ha, Shruti (IASSI Quarterly: Contributions To Indian Social Science)
Career choice not only affects the individual but also the society at large. Selection of one career is not only effected by intrinsic factors but is heavily guided by extrinsic factors also. - Reproduced
Keywords: Commitment, Gender, Resignation, Role conflict, Role perception, Skill, Vocation